2019
DOI: 10.1080/23311886.2019.1571730
|View full text |Cite
|
Sign up to set email alerts
|

A phenomenological study of employer perspectives on hiring ex- offenders

Abstract: Several researchers established a direct relationship between recidivism and ex-offenders' unemployment. While the consequences of ex-offender unemployment to society are known, the lived experiences of employers or business owners making employment decisions about ex-offenders were unknown. Using data obtained from in-depth interviews with employers who have considered hiring an ex-offender in the Baltimore Metropolitan area, this phenomenological study yielded findings that perception and trust played signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…While our data showed that participation in a WISE can help reduce stigma within the wider community (see also Svanberg et al, 2010;Roy et al, 2017;Krupa et al, 2019), this did not always translate into employment opportunities. For many of the partner organisations of SWORs, who would have been invaluable in supplying follow-on employment opportunities for the young people, there was great reluctance at taking the 'risk' in employing these 'ex-offenders' -a disinclination which has been extensively reported elsewhere (Gill, 1997;Williams, 2007;Haslewood-Pócsik, et al, 2008;Obatusin and Ritter-Williams, 2019). Not only did this further serve to consign young people to precariat, insecure employment opportunities, but it demonstrates a need for both 'intermediate' or 'transitional' companies and 'as end' (Vidal, 2005) WISE employers when working with criminalised youths.…”
Section: Discussionmentioning
confidence: 96%
“…While our data showed that participation in a WISE can help reduce stigma within the wider community (see also Svanberg et al, 2010;Roy et al, 2017;Krupa et al, 2019), this did not always translate into employment opportunities. For many of the partner organisations of SWORs, who would have been invaluable in supplying follow-on employment opportunities for the young people, there was great reluctance at taking the 'risk' in employing these 'ex-offenders' -a disinclination which has been extensively reported elsewhere (Gill, 1997;Williams, 2007;Haslewood-Pócsik, et al, 2008;Obatusin and Ritter-Williams, 2019). Not only did this further serve to consign young people to precariat, insecure employment opportunities, but it demonstrates a need for both 'intermediate' or 'transitional' companies and 'as end' (Vidal, 2005) WISE employers when working with criminalised youths.…”
Section: Discussionmentioning
confidence: 96%
“…But, running an ethical business, paying your tax properly, paying your suppliers, looking after your people, is all part of doing what we do. (PP02)This is a particularly important finding given that overcoming stigma is a key factor in addressing concerns about damage to organisational image (Obatusin and Ritter-Williams, 2019). A very contemporary feature of business was also reflected upon, that is how important it is to ‘Millennials’ 3 that businesses are aware of their social impact:Millennials are becoming a big part of the workforce and if you’re an employer and you want to attract clever millennials; you’ve got to be doing the right thing.…”
Section: The Benefits Of Recruiting Criminalised Peoplementioning
confidence: 96%
“…They described using six stages of data analysis to analyse the data. I found the six stages very detailed, structured, clear to follow and used in other research studies (Bynum et al 2019(Bynum et al , 2020Obatusin et al 2019). The stages were particularly informative in relation to how to apply the fourth step of the chosen framework of Fleming et al (2003), which is 'Gaining understanding through dialogue with text'.…”
Section: Choosing An Analytical Frameworkmentioning
confidence: 99%